ANALISIS FUNGSI MANAJEMEN DI MADRASAH ALIYAH (MA) ALI MAKSUM KRAPYAK YOGYAKARTA - Roizatul Faruk (Jurnal Pendidikan Agama Islam, 2014)
This study aimed to: 1) analyze the implementation of the management functions in Madrasah Aliyah Ali Maksum, 2) determine the implementation of the principles of management in the education component in Madrasah Aliyah Ali Maksum, and 3) determine the obstacles faced in the implementation of the management functions in Madrasah Aliyah Ali Maksum.The results of the analysis are as follows: 1) Management functions in Madrasah Aliyah Ali Maksum less effective / less to overall between the lower level with the top level. (2) The application of management principles in an educational component in Madrasah Aliyah Ali Maksum less effective, (3) The internal resistance is caused by the tradition of boarding schools, boarding schools and curriculum curriculum blend government. External barriers caused by the lack of coordination between organizations and Foundations Madrasa.